2016
DOI: 10.1186/s12866-016-0872-7
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-cysteine exhibits potent anti-mycobacterial activity in addition to its known anti-oxidative functions

Abstract: Background Mycobacterium tuberculosis infection is thought to induce oxidative stress. N-acetyl-cysteine (NAC) is widely used in patients with chronic pulmonary diseases including tuberculosis due to its mucolytic and anti-oxidant activities. Here, we tested whether NAC exerts a direct antibiotic activity against mycobacteria.MethodsOxidative stress status in plasma was compared between pulmonary TB (PTB) patients and those with latent M. tuberculosis infection (LTBI) or healthy uninfected individuals. Lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 52 publications
6
90
1
Order By: Relevance
“…In these experiments, L-cysteine or NAC where administered at a concentration of 4 mM, which is five times higher than the concentration we used in our experiments involving Mtb-infected macrophages. Indeed NAC administered at a concentration of 10 mM was shown to directly decrease Mtb replication (42). However, in this study, we show a reproduction of the experimental conditions indicated in Vilcheze et al (20), wherein cystamine or cysteamine, when administered at the concentrations used in Mtb-infected macrophages (400 and 800 µM, respectively), did not exert any direct activity against Mtb cultured in axenic media and did not prevent the emergence of drug tolerance against isoniazid.…”
Section: Discussioncontrasting
confidence: 43%
“…In these experiments, L-cysteine or NAC where administered at a concentration of 4 mM, which is five times higher than the concentration we used in our experiments involving Mtb-infected macrophages. Indeed NAC administered at a concentration of 10 mM was shown to directly decrease Mtb replication (42). However, in this study, we show a reproduction of the experimental conditions indicated in Vilcheze et al (20), wherein cystamine or cysteamine, when administered at the concentrations used in Mtb-infected macrophages (400 and 800 µM, respectively), did not exert any direct activity against Mtb cultured in axenic media and did not prevent the emergence of drug tolerance against isoniazid.…”
Section: Discussioncontrasting
confidence: 43%
“…Previous studies have suggested that active TB patients have an association with excessive oxidative stress with a decrease in antioxidant concentration and increased free radicals. 5,9 The oxidative environment normally helps to kill pathogenic microorganisms. However, in the intracellular pathogen of MTB, the opposite can grow well in macrophages in environments with high oxygen concentrations.…”
Section: Oxidative Stress In Tbmentioning
confidence: 99%
“…4 MTB infection can induce oxidative stress. 5 Oxidative stress results from an imbalance between reactive oxygen species (ROS) and antioxidants. Cells have several endogenous antioxidants as defense mechanisms, they are vitamin C, vitamin E and SOD enzymes, catalase, glutathione peroxidase, and endogenous thiol.…”
Section: Introductionmentioning
confidence: 99%
“…According to World Health Organization (WHO), anti-TB drugs are classified into five groups, based on evidence of efficacy, potency and drug class. In the frame of actual used DOTS (Directly Observed Treatment Short Course Chemotherapy) strategy 1,2 , the anti-tuberculosis (TB) treatment is standardized, meaning that all patients receive the same regimens, being included in well-defined groups. The standard treatment has advantages over individualized treatment by preventing prescription errors, appropriate appreciation of drug needs, distribution and monitoring 3,4 .…”
Section: Introductionmentioning
confidence: 99%